2013
DOI: 10.1128/jcm.01978-12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Accuracy of a PLEX-ID Flu Device for Simultaneous Detection and Identification of Influenza Viruses A and B

Abstract: Respiratory tract infections caused by influenza A and B viruses often present nonspecifically, and a rapid, high-throughput laboratory technique that can identify influenza viruses is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Among adult patients with ARI in one study using this type of testing in the United States in 2012-2013, 5% to 8% were found to sustain viral coinfections, to include influenza, HCoVs, RSV and HRV [35]. One influenza typing kit based on the RT-PCR electrospray ionization mass spectrometry (PCR-ESI-MS) platforms allows detection of all 16 hemagglutinin and 9 neuraminidase subtypes, [36] as well as detection of drift of specific genes over time [36][37][38][39]. Because of its ability to detect newly emerging recombinant, drifted, or shifted influenza viruses, the PCR-ESI-MS typing analysis can be useful in detecting newly emerging influenza strains [40].…”
Section: Diagnosismentioning
confidence: 99%
“…Among adult patients with ARI in one study using this type of testing in the United States in 2012-2013, 5% to 8% were found to sustain viral coinfections, to include influenza, HCoVs, RSV and HRV [35]. One influenza typing kit based on the RT-PCR electrospray ionization mass spectrometry (PCR-ESI-MS) platforms allows detection of all 16 hemagglutinin and 9 neuraminidase subtypes, [36] as well as detection of drift of specific genes over time [36][37][38][39]. Because of its ability to detect newly emerging recombinant, drifted, or shifted influenza viruses, the PCR-ESI-MS typing analysis can be useful in detecting newly emerging influenza strains [40].…”
Section: Diagnosismentioning
confidence: 99%
“…With carefully designed sequence primers, subtyping has become possible. Tang et al reported on the accuracy of the influenza A and B assay, PLEX-ID flu 29 . They found that the overall accuracy when evaluating the presence of either influenza A or B and if found to be influenza A subtyped as H1N1-p, H1N1-s, or H3N2 compared to a RT-PCR based assay Prodesse ProFLU+ for Influenza A or B typing, and Prodesse ProFAST+ for A subtyping to be 97.1-100%.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…These procedures are troublesome, however, fully automated analytical systems have been developed commercially involving polymerase chain reaction (PCR), sample preparation and ESI-MS for the detection of pathogens [15][16][17][18][19][20] . Another approach is introducing liquid chromatography (LC) for separation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Muddiman et al developed a software application to calculate the base composition from the accurate mass 43 . A similar program was integrated into the automated ESI-MS system [16][17][18] . The use of these algorithms may improve the robustness of the present method because a measured monoisotopic mass does not always correspond to a unique base composition owing to the mass tolerance of 3 ppm resulting from the inevitable measurement error.…”
mentioning
confidence: 99%
See 1 more Smart Citation